Preservation of Indonesian Culture through Indonesian Cultural Week - Rahimul Harahap; Emelda Tesanolika B.Manalu (Education Achievement: Journal of Science and Research, 2024)
Many cultures in Indonesia are very necessary to be preserved, especially in Elementary School of Langkat Multinational School, where the majority of students are foreign nationals, so this school holds Indonesian Cultural Week activities to preserve Indonesian culture. This research aims to describe the preservation of Indonesian culture through Indonesian Cultural Week activities held at Elemenary School of Langkat Multinational School. This research uses qualitative approach. The research was conducted at Elementary School of Langkat Multinational School. The samples in this study were principals, teachers, and students of 13 people determined by purposive sampling techniques. Data collection techniques using observation, interviews, documentation and field notes. Data analysis is done through data reduction, data presentation, and conclusion drawing. The results showed that the preservation of local culture at Elementary School of Langkat Multinational School was carried out very well through Indonesian Cultural Week activities with support from all relevant parties, namely principals, teachers, staff, students, and also parents, which was shown by the addition of students' level of knowledge about Indonesian culture.The conclusion of this research is that Indonesian Cultural Week activities can preserve local culture at Elementary School of Langkat Multinaional School in the good category. The implementation of Indonesian Cultural Week activities includes efforts to maintain local culture, cultural preservation based on needs, and there are strategies for cultural preservation. Supporting factors for the implementation of Indonesian Cultural Week activities are starting from the preparation stage which includes the preparation of the draft activities, budget funds, place and time of implementation and preparation of committee, up to the stage of implementation of activities and post-activity evaluation.